Violencia de género sobre inmigrantes en España. Un análisis psicosocial - Montañés, Pilar (2022)
In this article, gender -based violence inflicted on immigrant women in Spain is analyzed in a psychosocial framework. Three global objectives are fundamentally pursued. The first reviews some of the most important statistics at our disposal. The second describes the psychological and social factors related to the problem, emphasizing the barriers that immigrant women must systematically face, as well as the particular vulnerability of this group. And the third of fers a view of prostitution as a clear example of gender -based violence suf fered by many immigrant women. Finally , the most important contributions of social and behavioural science in general and of psychology in particular are discussed, suggesting some possible research initiatives for the future.